2023
DOI: 10.1097/md.0000000000034152
|View full text |Cite
|
Sign up to set email alerts
|

Age-stroke related dysfunction interaction associated with home discharge of stroke inpatients in the rehabilitation ward

Abstract: The purpose of this study was to investigate whether interactions exist among cognitive and physical functions and activities of daily living (ADL) associated with home discharge of stroke patients in the rehabilitation ward. The subjects were 231 patients with a first stroke. Age, gender, affected side, the stroke impairment assessment set, ADL and discharge destination were collected from the medical record. Using a decision tree, a combination of variables that might have an interaction effect associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Therefore, it increases the incidence of urinary incontinence. BI score 48 is used to assess the patient's ability to perform daily activities, In this study results showed that the risk of urinary incontinence in stroke patients with scores of ≤20 was 6.7 times higher than that in patients with scores of 21‐40, and 7.9 times higher than that in patients with scores of 41‐60, which indicates that stroke patients with moderate‐to‐severe functional impairment are limited by activities increases their likelihood of developing urinary incontinence 49 …”
Section: Discussionmentioning
confidence: 65%
“…Therefore, it increases the incidence of urinary incontinence. BI score 48 is used to assess the patient's ability to perform daily activities, In this study results showed that the risk of urinary incontinence in stroke patients with scores of ≤20 was 6.7 times higher than that in patients with scores of 21‐40, and 7.9 times higher than that in patients with scores of 41‐60, which indicates that stroke patients with moderate‐to‐severe functional impairment are limited by activities increases their likelihood of developing urinary incontinence 49 …”
Section: Discussionmentioning
confidence: 65%